Validation Study of Waray Text Readability Instrument - Voltaire Q. Oyzon; Juven B. Corrales; Wilfredo M. Estardo, Jr. (Institute of Advanced Engineering and Science, 2015)
In 2012 the Leyte Normal University developed a computer software—modelled after the Spache Readability Formula (1953) made for English—made to help rank texts that can is used by teachers or research groups on selecting appropriate reading materials to support the DepEd’s MTB-MLE program in Region VIII, in the Philippines. However, “several experiments have already established that existing readability measures in English cannot directly be used to compute readability of other languages.” To validate the Waray Text Readability Instrument (WTRI) formula, 15 stories were rated by 24 randomly selected teachers from two elementary schools in Tacloban City. The WTRI software uses two factors in determining readability, namely: (a) sentence length and (b) frequency of commonly occurring words. The teachers’ task is to read the given text and rate the grade level of each text by considering these three factors: (1) frequency of commonly used words; (2) sentence length; and, (3) total number of words. The data gathered was compared with the WTRI’s ratings of the same texts. Statistical testing was done to determine if there is a significant difference between the teachers’ rating of the texts and the WTRI’s ratings. As a result, there was no significant difference between the software’s grade level ratings and that of the teachers’. It implied that the WTRI’s calculation is valid.